Pengaruh Pemanfaatan Masker Alami Berbasis Yoghurt dan Air Cucian Beras terhadap Kesehatan Kulit Wajah - Ulya Khalisah; Nadya Kartika Putri Nainggolan; Siti Humairo (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
Staying in the house for a long time can cause facial skin to become dry and oily. The use of a face mask with yogurt and rice water which is rich in nutrients can help with dry or oily facial skin problems. The purpose of this study was to analyze the effect of natural masks based on yogurt and rice washing water on facial skin health. In this study, a quasi-experimental method was used. In this study, the dependent variable was facial skin and the independent variable was yogurt and rice washing water. The formulation of yogurt and washing water is 2:1. This mask was applied to 19 respondents who were observed before and after using a yogurt face mask and washing water. The skin moisture meter is used, namely the Ckeyin Fluorescence Detector, the average initial humidity is 41.56 and the end is 56.6, which means that facial skin moisture increases and the initial oil level is 31.21 and the end is 21.08, which means the facial oil level decreases. With the help of SPSS set the value of sig. below 0.05 and obtained sig. 0.00. The difference in the average initial and final results indicates that there is an effect of a natural face mask made from yogurt and rice washing water on the moisture and oil content of the face. Based on the organoleptic test through the regression test, the mean and standard error results for the aroma category are 3 ± 0,597; color category 3 ± 0.229; and texture category 3 ± 0.452. The data shows that respondents like the mask formula because it is obtained on a scale of 3 out of 4 and it can be concluded that natural face masks made from yogurt and rice washing water can improve facial skin health.